Psychiatric disorders in adolescent boys in detention: a preliminary prevalence and case-control study in two Chinese provinces - Zhou, J; Chen, C; Wang, X; Cai, W; Zhang, S; Qiu, C; Wang, H; Luo, Y; Fazel, S (2012)
We investigated the mental health of 232 consecutive receptions of juvenile boys aged 15-17 years in youth detention centers of two Chinese provinces and compared with juveniles in community settings. Interviews were conducted by psychiatrists using the Schedule for Affective Disorders and Schizophrenia for School-Age Children to diagnose DSM-IV psychiatric disorders. Of the 232 boys in detention, 188 (81.0%) met criteria for any psychiatric disorder, with 186 (80.2%) having a disruptive behavior disorder and 52 (22.4%) having a substance use disorder (SUD). High levels of comorbidity were observed with 38.8% being diagnosed with at least two disorders. The high absolute and relative risks of psychiatric disorders and SUDs suggest that the identification and treatment of such disorders in juvenile detention is a priority for service development. © 2012 Copyright Taylor and Francis Group, LLC.